P188 Survey of use of safety checklists and standardisation of practice in thoracoscopy centres in the UK. (12th November 2015) - Duncan, T; Clarke, S; Hoyle, J
Abstract : Introduction and objectives: Safety checklists have been part of routine surgical practice for some time with evidence for reduction in morbidity and mortality. The use of such checklists in physician led interventions is more of a novelty. Several recent papers have been published outlining the introduction of safety checklists in the field of cardiology and gastroenterology. The 2013 BTS bronchoscopy guidelines include an adapted WHO surgical checklist, but there are no such recommendations in the BTS pleural disease guidelines. A literature search did not reveal any evidence of use of safety checklists within the area of local anaesthetic thoracoscopy. Our department set out to adapt and introduce a safety checklist for use on our thoracoscopy list, and to ascertain whether such practice is common place on UK thoracoscopy lists. Additionally, we looked to assess whether other aspects of thoracoscopy practice were standard across the UK. Method: A checklist for use in thoracoscopy was adapted from the WHO surgical checklist. Additions specific to thoracoscopy included assessment of drain function post procedure. A brief survey was sent out electronically to 23 medical thoracoscopy practitioners throughout the UK. Questions assessed whether a safety checklist was in use, whether significant complications had occurred and whether MRSA screening and antibiotics prophylaxis were common practice. Results: A 35% response rate was achieved. 75% of participants were using pre procedure checklists. 63% of respondents had experienced issues with equipment malfunction or sterility. 75% of respondents had experienced significant clinical complications; death (12.5%), pleural space infection (50%), bleeding (25%), other (25%). MRSA screening was carried out in 50% of centres whilst prophylactic antibiotics were used in 25%. Conclusions: Amongst the responders there was a high rate of use of pre-procedure checklists. This may not be representative of practice throughout the UK due to the relatively low response rate. A significant proportion of respondents had experienced equipment related complications, something that is likely to be picked up during routine safety checks prompted by a checklist. The survey results suggest a lack of consistency in practice across the UK and more prescriptive guidelines may be beneficial.